Implementation Of Washing Program In Sustainable Water Management At Uin Raden Fatah Palembang - Khadijah, Nyayu; Falahudin, Irham; Yenrizal, Yenrizal; Rodiah, Siti; Ichsan, Chairul (Journal of Sustainability Perspectives, 2022)
This paper aims to explain and describe the implementation of the concept of sustainable water management applied at UIN Raden Fatah Palembang, as part of the implementation of the green campus idea. UIN Raden Fatah's participation in the UI GreenMetric program has been started since 2019 and will be active in 2020. Water management is an important thing at UIN Raden Fatah Palembang because of the condition of the campus itself which is in a water reservoir and swamp area. The campus is divided into two locations, namely Campus A in the Jalan Jenderal Sudirman area and Campus B in the Jakabaring area, Palembang. Campus B is a new campus that will only start operating in 2021, therefore, water management arrangements are very important. The management of water resources is carried out with the Wash program which consists of revitalizing clean water infrastructure, metering clean water supply, water reuse program, improving surface water quality, as well as construction of drainage and canalization. In practice, higher education leaders issue policies that involve all the academic community, ranging from education staff, educators, to students. Keyword: water, green campus, sustainable, swamp